2007
DOI: 10.1111/j.1742-7843.2007.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Acetaminophen Overdose Is Associated with Dose‐Dependent Hypokalaemia: A Prospective Study of 331 Patients

Abstract: Hypokalaemia is a recognized complication of acute acetaminophen overdose. It is unclear whether this might be a pharmacological effect of acetaminophen, or due to association with confounding factors. The present study sought to better characterize the relationship between acetaminophen concentrations and risk of hypokalaemia. A prospective study of patients received N-acetylcysteine treatment within 15 hr of acute acetaminophen ingestion. Serum potassium concentrations were determined before and after N-acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
14
0
2
Order By: Relevance
“…Hypokalaemia and mild metabolic acidosis may be direct effects of caffeine on sodium, potassium and proton handling in the proximal renal tubule, and confounding effects of paracetamol co-ingestion. 24,25 No effects on liver biochemistry occurred, and there was no significant effect on any of the electrocardiographic variables. These findings are reassuring from a safety perspective.…”
Section: Discussionmentioning
confidence: 94%
“…Hypokalaemia and mild metabolic acidosis may be direct effects of caffeine on sodium, potassium and proton handling in the proximal renal tubule, and confounding effects of paracetamol co-ingestion. 24,25 No effects on liver biochemistry occurred, and there was no significant effect on any of the electrocardiographic variables. These findings are reassuring from a safety perspective.…”
Section: Discussionmentioning
confidence: 94%
“…Appropriate secondary investigations should be considered in cases where there is diagnostic uncertainty or where an additional cause of acute renal failure is suspected. Hypokalaemia is a dose-dependent toxic effect of paracetamol, and potassium supplements may be required to maintain normal electrolyte status 14. Hydration and urinary volumes should be carefully observed and, in the presence of severe oliguria, then temporary haemodialysis may need to be considered 6…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the incorrect answers to Question 1B: (A) Ganciclovir resistance occurs in less than 3% of organ transplant recipients with CMV disease (15). In the VICTOR trial, there was equal development of resistance in the intravenous ganciclovir and oral ganciclovir groups at 1 year (13).…”
Section: Transplantation Question 1bmentioning
confidence: 99%
“…Renal dysfunction in the setting of acetaminophen overdose is most commonly a secondary complication of concomitant liver failure but can also occur in the absence of liver disease due to direct nephrotoxicity (14). Although there are no published reports of reversible proximal renal tubular acidosis with acetaminophen overdose, hypokalemia is a common electrolyte derangement observed in this setting (15)(16)(17)(18). In a retrospective study of 155 patients with paracetamol overdose a dose-dependent relationship was found between the admission paracetamol concentration and the fall in serum K ϩ concentration (18).…”
mentioning
confidence: 99%